Answer: 77 :)
Step-by-step explanation:
Answer:
3*72-139
216-139
77
you just multiple the parenthesis first
y=f(1/3x) & find new coordinates
Answer:
A(-3,0)
B(6,1)
C(15,0)
Step-by-step explanation:
To find the three new coordinates A,B,C we have to find out the equation of the original curve y=f(x) which is shown in the figure. We find that equation by using the turning point (2,1) which is point B and take any other point either A or C which intercept's the x-axis, i took C. We put both these points into the completing square formula of the curve.
[tex]y=a(x-h)^2+k[/tex]
where (h,k) are the turning points (2,1) respectively and C (5,0) corresponds to (x,y)
so the equations becomes
[tex]0=a(5-2)^2+1\\0=a(3)^2+1\\0=9a+1\\-1=9a\\a=\frac{-1}{9}[/tex]
So our equation y=f(x) becomes
[tex]y=-\frac{(x-2)^2}{9}+1[/tex]
now for
[tex]y=f(\frac{x}{3} )[/tex]
we replace the x in the original equation above with x/3 which changes the equation to
[tex]f(\frac{x}{3} )=-\frac{(\frac{x}{3}-2)^2}{9} +1[/tex]
and now we sketch the curve we have our hints for the new points A,B,C our hint is that the original points A and C are the x-intercepts so the new A and C lets name them A' and C' must be the x-intercepts as well and B is the turning point of y=f(x) so the new point B' must be the turning point of y=f(x/3)
so we simply sketch the curve y=f(x/3) use an online graph plotter if you know how to sketch it to save time or if you don't know you can ask me and i'll teach you cause learning to sketch isn't in the question so furthermore we sketch the curve i attached the figure in an image you check it out and the new points as well.
–4(5x)
simplify .......
Answer:
-20x.....
Step-by-step explanation:
–4(5x)
-20x
Given the point D(4,6), what is D' with R-90°
Answer:
D'( -6 , 4).
Step-by-step explanation:
In rotation through 90 degrees from the origin
P(x,y) - P'(-y , x)
D(4 , 6) - D'( -6 , 4).
It's simple
What single transformation was applied to triangle A
to get triangle B?
Answer: translation
Answer:
Translation
Step-by-step explanation:
Solve the following compound inequality
1. 2x + 12 > 10 or -2x>6
Answer:
6
Step-by-step explanation:equals 6
Solve the equation for the given variable.
2(x + 6) = 8
Please helppppp!!!!!
what is the gradient and vertical axis intercept of the linear equation y = 5x + 30
Gradient = Slope = coefficient of x
Thus ;
Gradient = Slope = 5
_________________________________
Vertical axis = y -axis
To find the y-intercept of the equation we must put zero instead of x .
Let's do it.....
[tex]y = 5x + 30[/tex]
[tex]y = 5(0) + 30[/tex]
[tex]y = 30[/tex]
So the y-intercept is 30 .
_________________________________
And we're done.....♥️♥️♥️♥️♥️
what is an equation of the line that passes through the points (-6,2)
and (-6,6)
. Diego pays $4.50 for 3 pounds of bananas and 2 pounds of oranges.
one pound of oranges cost $0.75 more than one pound of bananas
let b represent the price per pound of bananas.
Which equation represents the situation, and what is the price per pound of each fruit?
Answer:$14.75 for bananas and oranges
Step-by-step explanation:
You have to Add to get your answer.I'll show you how I got $14.75:
4.50+4.50=$9
9+2=$11
11+0.75=$11.75
11.75+3=14.75
Your answer is:$14.75
hope this was helpful:)
erics cell phone service costs $40.00 a month for unlimited calls. he also pays $0.02 for each text message he sends. what equation represents the total cost, c, in dollars, for when eric sends t text message
Answer:
40.021
Step-by-step explanation:
Unlimited calls = $40
Text message = $0.021
NOTE:There is a difference between the value you gave for cost of text messages in the question and the values given in the group of answers. I will use $0.021 for cost of text messages since it is common to all answer choices.
Total cost = Cost of unlimited calls + cost of text messages
C = $40 + $0.021
= $40.021
Therefore, the equation which represent the total cost in dollars for a month is 40.021
A. 40.021
Answer:
maluna1999live is correct the answer is 40.021 so if your going to give someone the brailest then it should be maluna1999live
Step-by-step explanation:
put these in order starting from the smallest 6^2,3^4,2^5,5^3
A 3.5 oz box of Raisenets costs 100 cents. How much is each oz (in cents)?
Consider the graph of the sixth-degree polynomial function f.
Replace the values b, c, and d to write function f.
f(x)=(x-b)(x-c)^2(x-d)^3
Answer:
f(x)=(x-1)(x+1)^2(x-4)^3
Step-by-step explanation:
The zeros of the function are x=-1, x=1, and x=4, so its factors are x+1, x-1, and x-4.
The graph touches, but doesn’t cross, the x-axis at x=-1. So the factor x+1 is a repeated factor with an even multiplicity.
The graph crosses the x-axis at x=4, but with a little curve before and after it meets this point. So the factor x+4 is a repeated factor with odd multiplicity.
The graph crosses the x-axis at x=1 with no curve before or after. So the factor x-1 is not a repeated factor.
Therefore, function f is defined by f(x)=(x-1)(x+1)^2(x-4)^3.
The sixth-degree polynomial that shows in the graph is [tex]\rm f(x) = (x+1)(x-1)^2(x-4)^3[/tex] and this can be determined by evaluating the x-intercept of the given graph.
Given :
Sixth-degree polynomial -- [tex]\rm f(x) = (x-b)(x-c)^2(x-d)^3[/tex]
The following steps can be used in order to determine the value of b, c, and d:
Step 1 - Write the given sixth-degree polynomial.
[tex]\rm f(x) = (x-b)(x-c)^2(x-d)^3[/tex]
Step 2 - Observe the given graph and determine the x-intercept of the graph of the sixth-degree polynomial.
Step 3 - So, the x-intercepts that are the values of b, c, and d is given below:
b = -1
c = 1
d = 4
Step 4 - Substitute the values in the given sixth-degree polynomial.
[tex]\rm f(x) = (x+1)(x-1)^2(x-4)^3[/tex]
For more information, refer to the link given below:
https://brainly.com/question/14375099
G(3b)=3(3b)+2
PLEASE SOLVE ASAP BUT CORRECT IN ITS NOT YOU WILL BE REMOVED!!!!!
Answer:
G(x) = 3x +2
Step-by-step explanation:
I do not know what the problem is asking for, but if it's asking for the function, here you go.
Answer:
shbdhsjdcjsvdbssegehehhehehejrjehe
State the number of complex roots, the number of positive real roots and the number of negative real roots of
x^4-x^3-6x+ 3 =0
9514 1404 393
Answer:
2 complex roots2 positive real roots0 negative real rootsStep-by-step explanation:
The signs of the terms are + - - +. There are two sign changes, so 0 or 2 positive real roots.
Negating the signs of the odd-degree terms, the signs are + + + +. There are no sign changes, so 0 negative real roots.
For x=0, the value of the quartic is +3. For x=1, the value is -3, so we know there are 2 positive real roots, one of which lies in the interval (0, 1).
The 4th-degree polynomial equation must have 4 roots, so the other two must be complex.
2 complex roots2 positive real roots0 negative real roots_____
The roots are approximately 0.489999841592, 2.06573034434, −0.777865092969 ± 1.53582061225i
Which table represents a linear function?
Answer:
a
Step-by-step explanation:
A delivery service defines a "package" as a parcel for the sum of the length and the girth is less than 70 in (length is the longest side of the package and the girth is the distance around the other two sides of the package) a box has a fixed girth of 24 in. Determine those lengths for which the box is considered a "package"
Answer:
Between 0 and 46 inStep-by-step explanation:
As per definition of the package
g + l < 70 in, where g- girth and l- lengthGiven the value of g
g = 24 inSo the value of l should be
24 + l < 70l < 70 - 24l < 46 inTo be considered a package the length to be less than 46 in
what is 53−(648)+102
Answer:
-493
Step-by-step explanation:
Answer:
-493:) brainly?
Step-by-step explanation:
What is the measure of the angles below?* 8x-3 6.x + 17
Answer:
x = 10
Step-by-step explanation:
Simplifying
8x + -3 = 6x + 17
Reorder the terms:
-3 + 8x = 6x + 17
Reorder the terms:
-3 + 8x = 17 + 6x
Solving
-3 + 8x = 17 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
-3 + 8x + -6x = 17 + 6x + -6x
Combine like terms: 8x + -6x = 2x
-3 + 2x = 17 + 6x + -6x
Combine like terms: 6x + -6x = 0
-3 + 2x = 17 + 0
-3 + 2x = 17
Add '3' to each side of the equation.
-3 + 3 + 2x = 17 + 3
Combine like terms: -3 + 3 = 0
0 + 2x = 17 + 3
2x = 17 + 3
Combine like terms: 17 + 3 = 20
2x = 20
Divide each side by '2'.
x = 10
Simplifying
x = 10
Five less than twice a number is greater than ten times a number.
Please help I have no clue what I'm looking at.
Answer:
5-2x>10x
Step-by-step explanation:
Answer:
bruh just reading this question hurts my head
i guess you could say the first number is 8 and the second number is 1, but jeez bro
Step-by-step explanation:
Candice has been hired as a saleswoman. She is paid a flat rate of $425 each week and earns an additional $17.75 commission for each sale. If her goal is to make $993 in one week, which equation will help Candice determine the number of sales (s) she must make? (3 points)
a
$993 = $425s - $17.75
b
$993 = $425s + $17.75
c
$993 = $17.75s - $425
d
$993 = $17.75s + $425
GIVING BRAINLIEST! Please help
Answer:
the marked answer is correct
Step-by-step explanation:
The desired end result is an identity matrix in the first three columns. The diagonal values are 1, as needed, so what remains is to eliminate the off-diagonal values. In row 2 that can be done by adding row 3 to it.
The next step should be to add rows 2 and 3 and replace row 2 with that sum.
If the coordinates of N are (5,6) and the midpoint of MN is (-1,4) then what are the coordinates of M?
Answer:
m-7 2
Step-by-step explanation:
I very much agree-_-
What are the x-intercepts of this function? f(x)=-9x^2+3x1
[tex] - 9 {x}^{2} + 3x = 0 [/tex]
[tex]3x( - 3x + 1) = 0[/tex]
[tex]3 x = 0 \\ x = 0[/tex]
And
[tex] - 3x + 1 = 0 \\ - 3x = - 1 \\ x = \frac{ - 1}{ - 3} \\ x = \frac{1}{3} [/tex]
So the x-intercepts are :
[tex]x = 0 \: \: \: \: \: and \: \: \: \: \: x = \frac{1}{3} \\ [/tex]
answer and I’ll leave a good review
Answer:
d
Step-by-step explanation:
g
Answer:
C
Step-by-step explanation:
They are all more in the modern era
Andrew rents bowling shoes for $4. He bowls 2 games. Andrew spent a total of $22. How much was the cost of each game, b? Complete the bar diagrams, and then solve the problem. Three bar graphs. Top bar on each is Total Spent. Bottom bar on each has 3 sections. The left section is labeled shoe rental, and each of the other sections is labeled cost per game. The cost per game sections are b. The other parts have fill-in boxes. Each game cost .
Answer:
2b + 4 = 22
b= 9, the cost of each game is $9
Step-by-step explanation:
13. Find g(f(5)) if g(x) = 2x - 7 and F(x) = -4x - 7
Answer:
g(f(5)) = - 61
Step-by-step explanation:
Evaluate f(5) then substitute the value obtained into g(x) , that is
f(5) = - 4(5) - 7 = - 20 - 7 = - 27 , then
g(- 27) = 2(- 27) - 7 = - 54 - 7 = - 61
In Science class, Sara needed 8 test tubes for 3 different experiments. The first
experiment required 2 test tubes and the other two experiments required the same
number of test tubes. How many test tubes were needed for each of the other two
experiments?
Answer:
3 test tubes
Step-by-step explanation:
First one took 2 so 8-2=6 so 6 left for the other 2 tests then 6 divided by 2 is 3
Solve showing steps. Use Insert equation to get the symbol and Ctrl with . For exponents x2 + 3x - 4 = 0 9x2 + 12x + 4 =0 (leave answer as a fraction) x2 - 2x - 3 = 0 x2 - 6x + 9 = 0 2x2 - 4x - 3 = 0 (round to two decimal places)*
Here all the given equations are in the form of
[tex]ax^2+bx+c=0[/tex]
The value of [tex]x[/tex] can be determined by the perfect square method as follows:
[tex]ax^2+bx+c=0[/tex]
[tex]\Rightarrow x^2+\frac{b}{a}+\frac{c}{a}=0[/tex]
[tex]\Rightarrow x^2+2\times\frac{b}{2a}+\left(\frac{b}{2a}\right)^2-\left(\frac{b}{2a}\right)^2+\frac{c}{a}=0[/tex]
[tex]\Rightarrow \left(x+\frac{b}{2a}\right)^2=\left(\frac{b}{2a}\right)^2-\frac{c}{a}[/tex]
[tex]\Rightarrow x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}\;\cdots(i)[/tex]
Now, for [tex]x^2+3x-4=0[/tex]
[tex]a=1, b=3, c=-4[/tex]
So, from equation (i)
[tex]x=\frac{-3\pm\sqrt{3^2-4\times1\times(-4)}}{2\times1}[/tex]
[tex]\Rightarrow x=\frac{3\pm\sqrt{9+16}}{2}[/tex]
[tex]\Rightarrow x=\frac{3\pm5}{2}[/tex]
[tex]\Rightarrow x=\frac{3+5}{2},\frac{3-5}{2}[/tex]
[tex]\Rightarrow x= 4, -1[/tex]
Similarly, for [tex]9x^2+12x+4=0[/tex]
[tex]a=9, b=12, c=4[/tex]
So, from equation (i)
[tex]x=\frac{-12\pm\sqrt{12^2-4\times9\times4}}{2\times9}[/tex]
[tex]\Rightarrow x=\frac{-12\pm0}{18}[/tex]
[tex]\Rightarrow x=\frac{-2}{3}[/tex]
For [tex]x^2-2x-3=0[/tex]
[tex]a=1, b=-2, c=-3[/tex]
[tex]x=\frac{-(-2)\pm\sqrt{(-2)^2-4\times1\times(-3)}}{2\times1}[/tex]
[tex]\Rightarrow x=\frac{2\pm\sqrt{16}}{2}[/tex]
[tex]\Rightarrow x=\frac{2\pm4}{2}[/tex]
[tex]\Rightarrow x=\frac{6}{2},\frac{-2}{2}[/tex]
[tex]\Rightarrow x=3.00, -1.00[/tex]
For [tex]x^2-6x+9=0[/tex]
[tex]a=1, b=-6, c=9[/tex]
[tex]x=\frac{-(-6)\pm\sqrt{(-6)^2-4\times1\times9}}{2\times1}[/tex]
[tex]\Rightarrow x=\frac{6\pm0}{2}[/tex]
[tex]\Rightarrow x=3.00[/tex]
For [tex]2x^2-4x-3=0[/tex]
[tex]a=2, b=-4, c=-3[/tex]
[tex]x=\frac{-(-4)\pm\sqrt{(-4)^2-4\times2\times(-3)}}{2\times2}[/tex]
[tex]\Rightarrow x=\frac{4\pm\sqrt{40}}{4}[/tex]
[tex]\Rightarrow x=\frac{4\pm2\sqrt{10}}{4}[/tex]
[tex]\Rightarrow x=\frac{4+2\sqrt{10}}{4},\frac{4-2\sqrt{10}}{4}[/tex]
[tex]\Rightarrow x=2.58, -0.58[/tex]